(untitled) (Research, Society and Development, 2022)
The aim of the present study is to describe the actions performed in the discipline Family Health Internship in the 7th period of the Dentistry undergraduate course at the State University of Montes Claros - UNIMONTES. This is an experience report carried out by the students, where actions were performed for the community. The data of the situational diagnosis were obtained through direct observation of the students in visits and interviews with the local preceptor, as well as consultation of the reports produced by the territorialization in force in the ESF. Before entering the territory, the students had the opportunity to meet with the local preceptor to have access to the situational diagnosis, which provided the development of an action plan that aimed to solve the following aspects found in the diagnosis: large number of elderly, hypertensive, diabetics, smokers, low adherence of pregnant women to prenatal dental care, lack of relevant actions that encourage collaborative work, and mental health problems. Activities were developed according to the problems presented in the situational diagnosis so that they could be solved or minimized. Despite the limitations, physical space available, participation of the population in the proposed actions and the pandemic period, the students learned a lot about the functioning of the ESF, characterizing the experience as a positive complement in the training process and in the transformation of the community.